Synchronous web-based collaborative writing: Attitudes of learners toward working in pairs and small groups - Emil Fermin Ubaldo (Universitas Syiah Kuala, 2021)
This study explored learners' attitudes toward collaborative writing in pairs and small groups (fours and sixes) in a synchronous web-based environment. Sophomore pre-service teachers in one intact class in the Philippines (n=31) completed the same collaborative writing tasks using Google Docs. In three separate out-of-class sessions, they first worked in pairs, and then they were assigned to either groups of four or groups of six in the succeeding two sessions. After completing the tasks, they were asked to complete a post-task questionnaire. The learners had an overall positive attitude toward peer collaborative writing in a web-based synchronous environment as it helps them to develop the content better, find appropriate vocabulary, and improve the grammatical and mechanical accuracy of the texts they produced. Students highly appreciated working in pairs and groups of four. In pairs, they felt that it is easier to manage text-chat deliberation, resolve concerns, and attend to each other's suggestions. In groups of four, they acknowledged the increase of peer resources for knowledge sharing and in ensuring the accuracy of their language use. Hence, the majority complained that a group of six is not that conducive in a real-time text-chat environment. When asked about their preference, most students would prefer to work in a similar task and environment in pairs. These findings on learners' attitudes toward collaborative writing concur with the previous literature in face-to-face educational settings and open new insights on synchronous web-based collaborative writing via text-chat.